2011
DOI: 10.1143/jpsjs.80sa.sa110
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study on AmO2: Comparison with UO2and NpO2

Abstract: Recently, 17 O NMR has been performed for the first time on AmO 2 . We have observed a drastic broadening of the NMR spectrum, along with a sudden drop of NMR signal intensity, below T 0 = 8.5 K. These data provide the first microscopic evidence for a phase transition at this temperature as a bulk property of this system. In this paper, we compare NMR results for AmO 2 with those from UO 2 and NpO 2 . In the ordered state we have recorded an 17 O NMR spectrum with a triangular line shape, which resembles neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…similar studies on the rare-earth-bearing compounds). The shifts measured here were compared with those reported in static conditions by Tokunaga et al , and Eastman et al For UO 2 , NpO 2 , and PuO 2 , the results are quite similar. For AmO 2 , the difference in shift is probably caused by the differences in the samples themselves (e.g., stoichiometry and irradiation-induced damage) and also by the heating induced by the sample rotation.…”
Section: Resultssupporting
confidence: 81%
“…similar studies on the rare-earth-bearing compounds). The shifts measured here were compared with those reported in static conditions by Tokunaga et al , and Eastman et al For UO 2 , NpO 2 , and PuO 2 , the results are quite similar. For AmO 2 , the difference in shift is probably caused by the differences in the samples themselves (e.g., stoichiometry and irradiation-induced damage) and also by the heating induced by the sample rotation.…”
Section: Resultssupporting
confidence: 81%
“…101 Notably, there are many existing experimental challenges to distinguish the essential bulk contribution of AmO 2 due to the strong self-radiation damage caused by alpha decay. [102][103][104][105] For the next actinide dioxide CmO 2 , only a few experiments have thus far been reported for the detailed constitution of its ground state. 19,106 Cm 4+ has six electrons in the 5f shell, producing a nonmagnetic 7 F 0 ground state from Hund's rules.…”
Section: Splitting Of One Electron Orbital (Schematic)mentioning
confidence: 99%
“…Similar to NpO 2 , Mössbauer spectroscopy [33] and neutron diffraction measurements failed to detect any magnetic order below T 0 = 8.5 K in AmO 2 [34]. However, NMR measurements on AmO 2 performed by Tokunaga et al [14,15] confirmed the phase transition seen at T 0 , although the NMR spectrum of AmO 2 is rather different from that seen in the AFM ground state of UO 2 [217] or the multipolar ground state of NpO 2 [218].…”
Section: Magnetic Propertiesmentioning
confidence: 93%
“…Over the course of the experiment, significant NMR intensity change occurred, indicating the electronic ground state is extremely sensitive to disorder induced by selfirradiation through the decay of Am [14]. Moreover, the NMR spectrum of AmO 2 is rather different from that seen in the AFM ground state of UO 2 or the multipolar ground state of NpO 2 [218]. The intense radioactivity and self-induced disorder present in any AmO 2 powder sample make experimentation particularly delicate and, thus, limit the available experimental techniques.…”
Section: Magnetic Properties Of Actinide Dioxidesmentioning
confidence: 96%